Two-step fabrication of iron-containing polyaniline composites for electrocatalytic hydrogenation of nitroarenes - Ivanova, N. M.; Visurkhanova, Ya. A.; Soboleva, E. A.; Kenzhetaeva, S. O. (Elsevier B.V., 2018)
Polyaniline+Fe+FeO+Fe3O4 composites were prepared as powder by a two-step process: (1) introduction of FeO into oxidative polymerization of aniline and (2) electrochemical reduction of the powder deposited on a Cu cathode in aqueous NaOH. The structure and morphological features were studied by atomic emission spectroscopy, X-ray diffraction analysis and electron microscopy. The polyaniline–iron composites were used in electrohydrogenation of p‑nitrobenzoic acid (p‑NBA). Their electrocatalytic activity in the process is due to the formation of iron particles as a result of the electrochemical reduction of Fe2+ cations in FeO. The electrocatalytic activity is clearly demonstrated by the electrocatalytic hydrogenolysis of the intermediate hydroxylaminobenzoate to the aminobenzoate. Magnetic properties have been determined for the composite with optimal FeO content before and after the electrocatalytic hydrogenation of p‑NBA.
Keywords: Polyaniline–iron composites; Iron (II) oxide; Electrocatalytic hydrogenation; p‑Nitrobenzoic acid; Magnetic properties